Major gastrointestinal bleeding in patients receiving anticoagulant therapy for venous thromboembolism. Issue 214 (June 2022) - Catella, Judith; Bertoletti, Laurent; Moustafa, Farès; Nieto, José Antonio; Valle, Reina; Pedrajas, José María; Villalobos, Aurora; Quere, Isabelle; Sarlon-Bartoli, Gabrielle; Monreal, Manuel; ,
Abstract: Introduction: The gastrointestinal (GI) tract is a frequent site of bleeding in patients receiving anticoagulant therapy for venous thromboembolism (VTE). At-risk patients have not been consistently identified yet. Methods: We used the RIETE registry to assess the clinical characteristics of patients developing major GI bleeding during the course of anticoagulation. Then, we built a predictive score based on multivariable analysis, aiming to identify patients at increased risk for major GI bleeding. Results: We included 87, 431 patients with acute VTE. During the course of anticoagulation, 778 (0.89%) suffered major GI bleeding, 815 (0.93%) non-major GI bleeding and 1462 (1.67%) had major bleeding outside the GI tract. During the first 30 days after major GI bleeding, 7.6% of patients re-bled, 3.9% had VTE recurrences and 33% died. On multivariable analysis, male sex, age ≥70 years, initial VTE presentation as pulmonary embolism, active cancer, prior VTE, recent major bleeding in the GI tract, esophageal varicosities, anemia, abnormal prothrombin time, renal insufficiency and use of corticosteroids were associated to an increased risk for major GI bleeding. Using the predictive score, 39, 591 patients (45%) were at low risk; 36, 602 (42%) at intermediate-risk; 9315 (11%) at high-risk; and 1923 (2.2%) at very high risk. Their rates of major GI bleeding were: 0.21%, 0.96%, 2.41% and 6.08%, respectively. The c-statistics was 0.771 (95%CI. 0.755–0.786). Conclusions: We have developed a score which has the potential to identify patients at increased risk for GI bleeding, but needs to be externally validated." Highlights: The gastrointestinal (GI) tract is a frequent site of bleeding in patients receiving anticoagulant therapy for VTE. At-risk patients have not been consistently identified yet. We used the RIETE registry to assess the incidence and severity of major GI bleeding during anticoagulation for VTE. Among 87, 431 patients with VTE, 0.9% suffered major GI bleeding. Of these, 33% died within the first 30 days after bleeding. We built a predictive score to predict the risk of major GI bleeding, c-statistics: 0.771 (95%CI. 0.755-0.786).